Alu fossil relics--distribution and insertion polymorphism. - Arcot, S S; Adamson, A W; Lamerdin, J E; Kanagy, B; Deininger, P L; Carrano, A V; Batzer, M A

(untitled) (Genome Research, 1996)
Screening of a human genomic library with an oligonucleotide probe specific for one of the young subfamilies of Alu repeats (Ya5/8) resulted in the identification of several hundred positive clones. Thirty-three of these clones were analyzed in detail by DNA sequencing. Oligonucleotide primers complementary to the unique sequence regions flanking each Alu repeat were used in PCR-based assays to perform phylogenetic analyses, chromosomal localization, and insertion polymorphism analyses within different human population groups. All 33 Alu repeats were present only in humans and absent from orthologous positions in several nonhuman primate genomes. Seven Alu repeats were polymorphic for their presence/absence in three different human population groups, making them novel identical-by-descent markers for the analysis of human genetic diversity and evolution. Nucleotide sequence analysis of the polymorphic Alu repeats showed an extremely low nucleotide diversity compared with the subfamily consensus sequence with an average age of 1.63 million years old. The young Alu insertions do not appear to accumulate preferentially on any individual human chromosome.